STUDI PALINOLOGI FORMASI MENTAWIR, SUB CEKUNGAN KUTAI BAWAH, KALIMANTAN TIMUR - Christina Ani Setyaningsih (Widyariset, 2009)
Palynological study of the Mentawir Formation, Lower Kutai Basin, East Kalimantan has been conducted on the 27 selected cutting samples of the 'X' Well in the depth of interval 100'-4.140 'which is situated in 'DNA' Field The purpose of this study is to determine the age and depositional environment and biostratigraphic sequence of the sediment. The age of the sediment is primarily marked by the last appearance of Florschuetzia trilobata at 850', range from Middle Miocene to Late Miocene. The Middle Miocene age occupies sediments from interval 850'-4.140 , whilst the Late Miocene  age covers sediments from interval 100'-850'. Delta environment of the interval samples were deposited in lower delta plain (distal) to the delta front (distal). Based on the changes on the amount of the taxa group in the mangrove and freshwater ecology as well as the changes in the sedimentation, thus the biostratigraphic sequence of the 2 X2 Well with depth of interval 100'- 4.140' in 2 DNA2 field lies in the Transgressive System Tract to the Highstand System Tract.